2016
DOI: 10.1007/978-1-4939-6685-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Diagnostics Using Purified Nucleic Acids

Abstract: Saliva is an easily accessible fluid that has led to increasing interest in the development of salivary diagnostics. This chapter describes some of the newer tools and procedures for collection, stabilization, and storage of oral fluid matrices that aid in the successful use of saliva as a test specimen. This chapter focuses particularly on nucleic acid components for downstream molecular diagnostic (MDx) testing, since this is probably the area where saliva is likely to have the greatest impact in improving h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Consequently, we chose to examine both homologues in the current study. A number of studies show that saliva is a reasonable target tissue for gene expression studies 68 including behavioral disorders 69 . The use of peripheral biomarkers, and gene expression, in particular, to better understand the combined role of genes, their pathways and environment, is gaining traction 70 in clinical psychiatry 71 , neurology 72 , drug discovery 73 , cancer treatment 74 and psychology 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we chose to examine both homologues in the current study. A number of studies show that saliva is a reasonable target tissue for gene expression studies 68 including behavioral disorders 69 . The use of peripheral biomarkers, and gene expression, in particular, to better understand the combined role of genes, their pathways and environment, is gaining traction 70 in clinical psychiatry 71 , neurology 72 , drug discovery 73 , cancer treatment 74 and psychology 53 .…”
Section: Discussionmentioning
confidence: 99%
“…One protocol recommended storing the supernatant from centrifuged saliva at cool temperatures but did not specify the temperature itself. 65 For cfDNA extraction from whole saliva, the recommended storage temperature is −80°C prior to DNA isolation. 65 The iSWAB-DNA Isolation Kit (Mawi DNA) allows for storage of samples for several months at ambient temperature.…”
Section: Introduction To Liquid Biopsymentioning
confidence: 99%
“… 65 For cfDNA extraction from whole saliva, the recommended storage temperature is −80°C prior to DNA isolation. 65 The iSWAB-DNA Isolation Kit (Mawi DNA) allows for storage of samples for several months at ambient temperature. 65 Stabilizing agents in other saliva collection tubes allow the samples to be stored at RT for up to a year.…”
Section: Introduction To Liquid Biopsymentioning
confidence: 99%
“…It has already been shown that saliva is a highly valid biological fluid that can be used for diagnostic applications [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%